E-002 Variability in the presence and origin of the ophthalmic artery in retinoblastoma patients. (22nd July 2018) - Quinn, C; Tummala, R; Male, S; Mehta, T; Tore, H; Jagadeesan, B
Abstract : Objective: The recent advancement of super-selective ophthalmic artery (OA) intra-arterial chemotherapy (IAC) for retinoblastoma (Rb) has provided significant benefit for pediatric retinoblastoma patients. 1 The usual anatomical origin of the OA along with common variations in its origination have been well described from the study of adult cadaveric specimens, as well as angiographic examinations on adult patients. 2–3 However, the variations in the origin of the OA in the pediatric population have not been well documented. Ever since IAC for Rb has started becoming first-line therapy, interventionalists have been given an opportunity to examine pediatric orbital blood supply and OA anatomy. The incidence of these variations in OA origin have become of more interest. We have observed in many of our pediatric patients, that the origin of the OA is highly variable and often appreciably more superior along the internal carotid artery (ICA) than in their adult counterparts. Herein, we describe the variability of the OA origin, not only in terms of its location along the ICA but also the stage of treatment at which it is detected to originate from the ICA. Methods: After institutional review board approval, a retrospective analysis was conducted of electronic medical records and imaging of our Rb population. Digital subtraction angiograms from treatment sessions were reviewed and the distance of OA origin from the anterior most point along the convex surface of the anterior genu of the cavernous ICA was measured. Results: A total of 20 patients and 67 eyes were treated with intra-arterial chemotherapy between 2011 and 2018. A total of 44 super-selective OA infusions were conducted, leaving 23 treatments through alternative routes. On average, the OA was seen to originate 4.6 mm (range 2.7 mm – 7.3 mm) above the anterior genu. There were three patients where the OA was not clearly present on the initial treatments. These patients were treated via alternative routes for their first two sessions, then subsequently, the OA was present and provided a clear choroidal blush upon injection. One patient did not have an OA for any of their four sessions. Conclusions: Within the Rb population, there is variability in OA presence and origin. In general, it appears to arise from a more superior position on the ICA than typically seen in adults. Additionally, in some children, the OA may be not be visible on initial DSA, but might manifest at a later stage during treatment. These findings suggest that there is post-natal maturation of the orbital blood supply before it settles into the typical adult pattern. References: Abramson DH, Dunkel IJ, Brodie SE, et al . A phase I/II study of direct intraarterial (ophthalmic artery) chemotherapy with melphalan for intraocular retinoblastoma. Ophthalmology 2008;115(8):1398–405. Hayreh SS, Dass R. The ophthlamic artery I. Origin and intra-canalicular course. Brit J Ophthal 1962;45(62). Michalinos A, Zogana S, Kotsiomitis E, et al . Anatomy of the ophthalmic artery: A review concerning its modern surgical and clinical applications. Anat Res Int 2015:1–8. Disclosures: C. Quinn: None. R. Tummala: None. S. Male: None. T. Mehta: None. H. Tore: None. B. Jagadeesan: 2; C; Microvention, Tustin, CA, Medtronic, Minneapolis, MN, CVRx, Minneapolis, MN.